2012
DOI: 10.1504/ijsn.2012.052540
|View full text |Cite
|
Sign up to set email alerts
|

Towards an understanding of the impact of advertising on data leaks

Abstract: Recent investigations have determined that many Android applications in both official and non-official online markets expose details of the user's mobile phone without user consent. In this paper, for the first time in the research literature, we provide a full investigation of why such applications leak, how they leak and where the data is leaked to. In order to achieve this, we employ a combination of static and dynamic analysis based on examination of Java classes and application behaviour for a data set of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Studying the scoring of LESK with respect to one of our most popular user interests in our L1 dataset we found it to be problematic. When comparing the matching goal workout with the category Health and Fitness, LESK assigns it one of the lowest scores (33), with the maximum score assigned to the (workout, books and references) pair (113).…”
Section: Nlp In Plutomentioning
confidence: 99%
See 1 more Smart Citation
“…Studying the scoring of LESK with respect to one of our most popular user interests in our L1 dataset we found it to be problematic. When comparing the matching goal workout with the category Health and Fitness, LESK assigns it one of the lowest scores (33), with the maximum score assigned to the (workout, books and references) pair (113).…”
Section: Nlp In Plutomentioning
confidence: 99%
“…Mobiles often contain sensitive information about user attributes which users might not comfortably share with advertising networks but could make valuable targeted data. This, in turn, led to a substantial line of research on privacy and advertising on mobiles in two general areas: (1) strategies for detection and prevention [53], [43], [17], [31], [33], [18], [50], [52], [7], [47], [48], [35], and (2) architectures and protocols that improve privacy protections [19], [36], [40], [29]. The first of these approaches primarily provides insights into the current practices of advertisers and advertising networks.…”
Section: Introductionmentioning
confidence: 99%
“…CrowDroid [9] is an offline analysis over traces that can be leveraged to identify malicious apps through examining their behavior via crowdsourcing. Moonsamy et al [27] provided a thorough investigation and classification of 123 apps using static and dynamic techniques over the apps' Java source code. Grace et al [21] showed that ad frameworks opportunistically scan and leverage permissions granted by the app they are called from.…”
Section: Related Workmentioning
confidence: 99%
“…crowdsourcing. Moonsamy et al [24] provided a thorough investigation and classification of 123 apps using static and dynamic techniques over the apps' Java source code. Grace et al [8] showed that ad frameworks opportunistically scan and leverage permissions granted by the app they are called from.…”
Section: Related Workmentioning
confidence: 99%